Colony size affects breeding density, but not spatial distribution type, in a seabird. (17th June 2020) - Bouwhuis, Sandra; Ballani, Felix; Bourgeois, Marie; Stoyan, Dietrich
Abstract: The spatial distribution of individuals within populations can result in fine-scale density dependence and affect the social environment that is encountered. As such, it is important to quantify within-population spatial structuring and understand the factors that shape it. In this study, we make use of point process statistics to test whether colony size affects the statistical type of spatial nest distribution produced by common terns ( Sterna hirundo ) breeding at identical manmade rectangular and homogeneous islands of fixed physical size. Comparing subcolonies of variable density both within and across years, we find that inter-nest distances are smaller at higher local and overall breeding density, but that the spatial distribution type does not vary across the observed densities. This suggests that the birds' main settlement rules do not depend on density. In our case, analyses of fine-scale density dependence or potential social effects therefore do not need to account for between-individual heterogeneity in settlement decision rules or acceptance of these rules. We urge, however, other studies to similarly test for density dependence of the spatial distribution of individuals before undertaking such "downstream" analyses. Abstract : The way individuals are distributed across their environment affects their behavior and performance but may itself depend on behavior and performance as well. Comparing subcolonies of variable density both within and across years, our study on common tern nest patterns shows that inter-nest distances are smaller at higher local and overall breeding density but that the spatial distribution type does not vary. As such, all individuals seem similarly affected by increased colony size.